2016
DOI: 10.5964/pch.v5i3.152
|View full text |Cite
|
Sign up to set email alerts
|

The tale of seeking treatment: A qualitative study of pulmonary tuberculosis patients

Abstract: Aim: The aims of the study were unravelling patients' health-seeking behaviour pathways to seek medication in healthcare facilities and key factors that determined patients' immediacy in seeking medical treatment. Method: By involving 5 pulmonary TB patients who were undertaking treatment at Pegirian Primary Health Centre, Surabaya, Indonesia, the research was carried out using an explorative qualitative research design, and the chosen data collection technique was semi-structured interview. Results:The resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 19 publications
0
7
0
1
Order By: Relevance
“…In most Indonesian communities, seeking care involves not only patients but also family, friends, and other community members [ 21 , 28 , 30 , 31 , 34 , 35 , 38 , 45 , 55 , 59 , 64 , 67 , 72 ]. Recommendations from significant others were associated with visiting alternative health-care providers for treating tuberculosis [ 21 ] and cancer [ 28 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…In most Indonesian communities, seeking care involves not only patients but also family, friends, and other community members [ 21 , 28 , 30 , 31 , 34 , 35 , 38 , 45 , 55 , 59 , 64 , 67 , 72 ]. Recommendations from significant others were associated with visiting alternative health-care providers for treating tuberculosis [ 21 ] and cancer [ 28 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ketika DOTS diterapkan secara komprehensif, ada kepercayaan dari pasien untuk mengikuti pengobatan di suatu faskes, mengingat pengobatan TB yang membutuhkan waktu 6 bulan untuk mencapai kesembuhan. Pasien juga merasa mendapatkan informasi yang cukup dan dukungan saat pengobatan (Suhariadi et al, 2016;Getahun and Nkosi, 2017). Kelebihan RS Swasta dibanding faskes milik pemerintah seperti puskesmas adalah respon lebih cepat, waktu bisa lebih fleksibel dan pelayanan lebih lengkap (Putri and Hisyam, 2014).…”
Section: Pembahasanunclassified
“…Based on prior research on patients’ health-seeking behavior in Indonesia,13,14 lay knowledge of pulmonary TB is found to have a significant effect on several preventive health-related behaviors. Various prior research have also demonstrated that lack of lay knowledge is associated with less motivation to perform preventive behaviors,15 less chance to seek treatment,16,17 longer treatment delay,9,18,19 and higher social stigma 20,21.…”
Section: Introductionmentioning
confidence: 99%
“… 12 , 23 26 Other research studies based in Indonesia mention that knowledge of pulmonary TB is generally poor regardless of their education level. 14 , 26 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation